2016
DOI: 10.1016/j.immuni.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Landscape of Human Tissue Lymphocytes Unveils Uniqueness of Tumor-Infiltrating T Regulatory Cells

Abstract: SummaryTumor-infiltrating regulatory T lymphocytes (Treg) can suppress effector T cells specific for tumor antigens. Deeper molecular definitions of tumor-infiltrating-lymphocytes could thus offer therapeutic opportunities. Transcriptomes of T helper 1 (Th1), Th17, and Treg cells infiltrating colorectal or non-small-cell lung cancers were compared to transcriptomes of the same subsets from normal tissues and validated at the single-cell level. We found that tumor-infiltrating Treg cells were highly suppressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
576
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 560 publications
(618 citation statements)
references
References 56 publications
(58 reference statements)
39
576
3
Order By: Relevance
“…In patients suffering from various malignancies, alterations in the TME similar to the ones we found here in the presence of Prkch -/-Tregs correlate with better survival and response to treatment (2)(3)(4)(5)(6). A recent transcriptome analysis of T cell subsets purified from clinical samples of colorectal and lung tumors identified CTLA4 and PAK2 as part of a gene signature specifically upregulated in tumor-infiltrating Tregs (60). Importantly, CTLA4 and PAK2 mRNA levels were higher in tumor-infiltrating Tregs than in Tregs purified from the surrounding, nontumoral tissues or from the blood, as well as in Teff cells purified from the surrounding tissue, peripheral blood, or even from tumor-infiltrating Teff cell subsets (60).…”
Section: Cd11bsupporting
confidence: 78%
See 1 more Smart Citation
“…In patients suffering from various malignancies, alterations in the TME similar to the ones we found here in the presence of Prkch -/-Tregs correlate with better survival and response to treatment (2)(3)(4)(5)(6). A recent transcriptome analysis of T cell subsets purified from clinical samples of colorectal and lung tumors identified CTLA4 and PAK2 as part of a gene signature specifically upregulated in tumor-infiltrating Tregs (60). Importantly, CTLA4 and PAK2 mRNA levels were higher in tumor-infiltrating Tregs than in Tregs purified from the surrounding, nontumoral tissues or from the blood, as well as in Teff cells purified from the surrounding tissue, peripheral blood, or even from tumor-infiltrating Teff cell subsets (60).…”
Section: Cd11bsupporting
confidence: 78%
“…A recent transcriptome analysis of T cell subsets purified from clinical samples of colorectal and lung tumors identified CTLA4 and PAK2 as part of a gene signature specifically upregulated in tumor-infiltrating Tregs (60). Importantly, CTLA4 and PAK2 mRNA levels were higher in tumor-infiltrating Tregs than in Tregs purified from the surrounding, nontumoral tissues or from the blood, as well as in Teff cells purified from the surrounding tissue, peripheral blood, or even from tumor-infiltrating Teff cell subsets (60). Similar observations were made for PAK2 in breast carcinoma and hepatocellular carcinoma clinical samples (61,62).…”
Section: Cd11bmentioning
confidence: 99%
“…For example, local T reg cells in the TME of human tumors also show upregulated expression of PD-L1 and PD-L2 (ref. 37), and therefore, might be affected by PD-1 blockade; if this is the case, then alterations in T reg cell activity might contribute to both PD-1-and CTLA-4-induced autoimmunity. An anti-tumor immune response can kill tumor cells, and host APCs can then pick up the antigens, which, in a form of antigen presentation referred to as cross-presentation, leads to the priming of secondary immune responses.…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…The classical ligand for CCR8 are CCL1 and CCL18, however it has been shown that CCL17 also induces migration of CCR8-expressing cells 44 , which is relevant in the cancer field as CCL17 has been strongly associated with tumour progression 27 . Same year, two independent research groups also described CCR8 as one of the main chemokine receptor in Tregs present in breast 45 , colorectal and non-small-cell lung cancer 46 . Whereas Plitas et al, mentioned that tumour environment has the ability to potentiate CCR8 expression in Tregs, De Simone et al, discussed that the presence of CCL18 in different tumours might be associated with the migration of CCR8 + cells 45,46 .…”
Section: Regulatory Cd4 + Th-like Helper Cells In Cancermentioning
confidence: 99%
“…Same year, two independent research groups also described CCR8 as one of the main chemokine receptor in Tregs present in breast 45 , colorectal and non-small-cell lung cancer 46 . Whereas Plitas et al, mentioned that tumour environment has the ability to potentiate CCR8 expression in Tregs, De Simone et al, discussed that the presence of CCL18 in different tumours might be associated with the migration of CCR8 + cells 45,46 . In 2017, our research group characterized the presence of Th1, Th2, Th17 and Th1/17 Tregs in peripheral blood and several tissues, such as skin, colon, thymus, spleen and liver perfusates 31 .…”
Section: Regulatory Cd4 + Th-like Helper Cells In Cancermentioning
confidence: 99%